Rules versus home rule: Local government responses to negative revenue shocks - Stan Veuger; Daniel Shoag; Cody Tuttle (American Enterprise Institute (AEI), 2019)
Local governments rely heavily on sales tax revenue. We use national bankruptcies of big-box retail chains to study sudden plausibly exogenous revenue shortfalls. Treated localities respond by reducing spending on law enforcement and administrative services. We further study how cities with different degrees of autonomy vary in their response. Cities in home rule states react more swiftly by raising taxes or issuing bonds. A regression discontinuity analysis of cities in Illinois emphasizes that this effect of local autonomy is causal. Home rule cities do not abuse their discretion: their bond ratings are more likely to be strong.
Keywords: A; 330; State taxes; revenue; Local government